Menumbuhkan Budaya Religius: Pendekatan Guru PAI dalam Pendidikan Karakter - Fajri, Nur; Ardianto, Ardianto; Sholihah, Maidatus (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2025)
This study examines the strategy of Islamic Religious Education (PAI) teachers in fostering a religious culture in students at MIN 11 Banda Aceh. This research is a qualitative study with a case study approach. Data were collected through observation, in-depth interviews, and documentation of PAI teachers, madrasah heads, and students in grades II, V, and VI, totaling 73 people. The results showed that PAI teachers instill a religious culture through habituation strategies, exemplary motivation, and open communication. The three central values developed include honesty, humility, and discipline. The value of honesty is instilled through teacher examples and contextual Islamic stories. The value of humility is strengthened through the 5S culture (smile, greeting, greeting, politeness, courtesy), visual media such as posters, and community involvement. Meanwhile, the value of discipline is developed through scouting activities, exemplary teachers, and persuasive approaches to enforcing rules. The study also found several internal obstacles, such as limited worship facilities and low student interest, and external, such as lack of communication with student guardians and the negative influence of digital media. This study recommends the need for synergy between madrasah, parents, and the community to support the implementation of a religious culture. Madrasahs are also advised to strengthen religious facilities and conduct character development more sustainably and participatory manner. This study is expected to be a reference in developing Islamic character education strategies in primary madrasahs.